2016
DOI: 10.1614/ws-d-15-00125.1
|View full text |Cite
|
Sign up to set email alerts
|

Palmer Amaranth (Amaranthus palmeri) Identification and Documentation of ALS-Resistance in Argentina

Abstract: Palmer amaranth has greatly disrupted agricultural practices in the United States with its rapid growth and rapid evolution of herbicide resistance. This weed species is now suspected in Argentina. To document whether the suspected plant populations are indeed Palmer amaranth, molecular comparisons to known standards were conducted. Additionally, these same plant populations were screened for possible herbicide resistance to several acetolactate synthase (ALS)-inhibiting herbicides. Sequencing data confirmed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 34 publications
1
29
0
5
Order By: Relevance
“…Merr. ), corn ( Zea mays L.) and cotton ( Gossypium hirsutum L.), all on the American continent . Amaranthus species are characterized by having an extended period of germination, rapid growth, and prolific seed production .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Merr. ), corn ( Zea mays L.) and cotton ( Gossypium hirsutum L.), all on the American continent . Amaranthus species are characterized by having an extended period of germination, rapid growth, and prolific seed production .…”
Section: Introductionmentioning
confidence: 99%
“…7 In Argentina, mucronate amaranth (Amaranthus quitensis L.) is largely considered the most problematic weed of recent times, with no official reports of the presence of A. palmeri until 2013. 13,25 Given the high tendency of A. palmeri to acquire resistance to several mechanisms of action, it is highly relevant to characterize the reported field resistances and carry out detailed studies of the molecular basis of these resistances. This information will be useful in designing control strategies that allow farmers to prevent, understand and overcome this weed resistance problem without creating a similar one in the near future.…”
Section: Introductionmentioning
confidence: 99%
“…The remaining individuals tested showed no mutations at these positions (Supplementary Information Table 1 ). Both mutations have been reported before in A. palmeri from Mississippi, United States, and Brazil ( Molin et al, 2016 ; Küpper et al, 2017 ) while only S 653 N was reported from GA ( Berger et al, 2016 ). The mutation at W 574 L is known to confer resistance to triazolopyrimidines, sulfonylureas, imidazolinones, and pyrimidinylthio-benzoates (including pyrithiobac-sodium), whereas the S 653 N mutation confers resistance to imidazolinones and the pyrimidinylthio-benzoates only ( McNaughton et al, 2005 ; Whaley et al, 2006 ; Patzoldt and Tranel, 2007 ; Laplante et al, 2009 ; Yu et al, 2012 ).…”
Section: Resultsmentioning
confidence: 74%
“…A major management question for growers is how much of the resistance issue results from previous selection intensity from management practices in their own fields, and how much results from gene flow from neighboring fields. Although this study was not able to definitively determine whether AZ-R evolved independently or if glyphosate resistance migrated to AZ, the recent geographical expansion of A. palmeri to the upper United States Midwest ( Kartescz, 2014 ), Argentina ( Berger et al, 2016 ), and Brazil ( Küpper et al, 2017 ) shows that migration via seed movement is an important factor for A. palmeri . Long-distance seed dispersal is possible through irrigation and rainfall events ( Norsworthy et al, 2014 ), buying and selling of used harvest equipment, custom harvesting crews moving around the country ( Schwartz et al, 2016 ), contaminated crop seed and feed, as well as transportation through migrating wildlife such as ducks and geese ( Farmer et al, 2017 ).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation